Determination of Natural Radionuclides (Ra-226, Po-210, Ra-228 and K-40) and Cs-137 in Fish Consumed in the City of São Paulo (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The aim of the study was to determine the activity concentration of the natural radionuclides (226Ra, 210Po, 228Ra and 40K) and artificial radionuclide 137Cs in the muscle of the marine fish species most consumed in the city of São Paulo and to evaluate the annual effective dose due to the consumption of the fish. Samples were collected in the supermarket chain Extra and Carrefour and in the distribution center CEAGESP. Six fish species were selected among the most available and consumed in São Paulo city: anchovy, tuna, dogfish, croaker, hake and sardine. After the sample preparation procedures, the determination of 226Ra, 228Ra, 40K and 137Cs was carried out by gamma spectrometry and the determination of 210Po by alpha spectrometry. The results obtained for all the species studied are below the limits adopted by the Brazilian Standards for 137Cs and, therefore, their consumption offers no risk due to the ingestion of this radionuclide. The concentration obtained for the radionuclides 226Ra, 210Po, 228Ra and 137Cs in the fish samples analized are low and of the same order of magnitude as data from literature. The results obtained for the doses, for all the species studied, showed that their consumption offers no risk of exposure due to the ingestion of the analyzed radionuclides.